The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-61813-6
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-controlled self-assembly of tetrapodal [4 + 4] phosphate organic molecular cage

Abstract: Two flexible subcomponents, namely tris(4-formylphenyl)phosphate and tris(2-aminoethyl)amine, are assembled into a tetrapodal [4 + 4] cage depending on the solvent effect. Single-crystal structure analysis reveals that the caivity is surrounded by four phosphate uints. Good selectivity of CO2 adsorption over CH4 is demonstrated by the gas adsorption experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Overall, NHD could obviously decrease the energy barrier for the regeneration of carbamate by Reaction II (a) and (b) (Figure S15), which is caused by the solvent effect of NHD. 38,39 Generally, molecular H 2 O has higher polarity than that of NHD, resulting in more stable hydrogen bonds between H 2 O and DMPA. These hydrogen bonds might decrease the electron density around N (DMPA), leading to the reduction in the nucleophilicity or alkalinity of DMPA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Overall, NHD could obviously decrease the energy barrier for the regeneration of carbamate by Reaction II (a) and (b) (Figure S15), which is caused by the solvent effect of NHD. 38,39 Generally, molecular H 2 O has higher polarity than that of NHD, resulting in more stable hydrogen bonds between H 2 O and DMPA. These hydrogen bonds might decrease the electron density around N (DMPA), leading to the reduction in the nucleophilicity or alkalinity of DMPA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally speaking, the larger the difference in size, the more easily separation can be achieved. Therefore, the separation of gas pairs with a relatively profound size difference, such as CO 2 / N 2 34,35 and CO 2 /CH 4 , 36,37 is straightforward using POCs.…”
Section: Separation Of Gases With a Small Size Differencementioning
confidence: 99%
“…Many studies have reported the ideal selectivity in gas pairs of CO 2 /N 2 or CO 2 /CH 4 achieved by POCs; the ideal selectivity value of the CO 2 /N 2 pair ranges from B10 to 200, 34,35,[38][39][40][41][42] at standard temperatures (273-298 K) and pressure (1 bar), whereas the reported selectivity of CO 2 /CH 4 ranges from B4 to B50. [36][37][38] The real challenge for separation is gas pairs with a small size difference. In Fig.…”
Section: Separation Of Gases With a Small Size Differencementioning
confidence: 99%
“…Huang et al recently reported profound solvent effect in the formation of OICs from trisformyl 6 and 1 . [ 12 ] When the reaction was carried out in MeCN with 1:1 molar ratio [2+3] imine cage 7 was obtained with characteristic peaks in ESI‐MS and 1 H NMR spectroscopy. But replacement of MeCN by CHCl 3 led to complete change of framework toward [4+4] imine cage 8 (Scheme 3).…”
Section: Aliphatic Triamine Based Oics: Syntheses Special Featurementioning
confidence: 99%